Protective Evaluation of Compounds Extracted from Root of Rhodiola rosea L. against Methylglyoxal-Induced Toxicity in a Neuronal Cell Line - Cheng-Hao Wang; Safwan Safwan; Min-Chi Cheng; Te-Yu Liao; Lin-Chen Cheng; Ting-An Chen; Yueh-Hsiung Kuo; Yung-Feng Lin; Ching-Kuo Lee (Molecules, 2020)
Rhodiola rosea L. (R. rosea) is one of the most beneficial medicinal plants and it is studied as an adaptogen. This study aims to evaluate the neuroprotective activity of compounds extracted from the root of R. rosea against methylglyoxal (MG)-induced apoptosis in neuro-2A (N2A) cells. The root of R. rosea was extracted with ethanol and partitioned with water, ethyl acetate, and n-butanol fractions to evaluate acetylcholinesterase (AChE) inhibitory activity and neuroprotective activity. The ethyl acetate fraction exhibited the highest values of AChE inhibitory activity (49.2% ± 3%) and cell viability (50.7% ± 4.8%) for neuroprotection. The structure identification of the most potential fraction (ethyl acetate fraction) revealed 15 compounds, consisting of three tannins, five flavonoids, and seven phenolics by infrared spectroscopy, nuclear magnetic resonance, and mass spectroscopy. All compounds were evaluated for their neuroprotective activity. Salidroside had the most potential neuroprotective activity. Gallic acid and methyl gallate had potential cytotoxicity in N2A cells. This study showed that R. rosea might have potential neuroprotective activities.